MANAJEMEN SARANA DAN PRASARANA DI MADRASAH TSANAWIYAH SWASTA (MTSS) NURUL HIKMAH - Muhammad Padlan; Muhammad Sapitra, Muhda Hadi Saputra, Sairi, Syahrani (CV. ADIBA AISHA AMIRA, 2023)
This research aims to evaluate PAI teacher performance management towards the development of student characteristics at Madrasah Tsanawiyah Anwarul Hasaniyyah. This research was conducted using quantitative research methods with techniques in the form of frequency distribution through questionnaires. The results of the research show that the performance management of PAI teachers at Madrasah Tsanawiyah Anwarul Hasaniyyah has been carried out well, especially in terms of lesson planning, learning implementation and learning evaluation. PAI teachers at Madrasah Tsanawiyah Anwarul Hasaniyyah have also implemented various creative and innovative learning methods to improve student characteristics, such as lecture, discussion, question and answer and simulation methods. However, there are still several obstacles in managing PAI teacher performance, such as a lack of adequate facilities and infrastructure. Therefore, it is recommended that the school can provide better support in terms of providing facilities and infrastructure, as well as providing training and competency development for PAI teachers to improve the quality of PAI teacher performance management and develop student characteristics at Madrasah Tsanawiyah Anwarul Hasaniyyah.